Current air quality plans in Europe designed to support air quality management policies - Miranda, Ana (2017)
The intensification of the human activity in urban areas as a result of the increasing population has contributed to the air pollution worsening in cities. To reverse this trend, the European Commission established a legal framework to improve the air quality. Thereby the Member States need to develop air quality plans (AQP) for zones and agglomerations where air quality limit values are exceeded, in order to implement pollution control strategies and meet the legal requirements. Understanding the reasons for the levels of air quality non–compliance as well as evaluating available and commonly used tools to predict the air quality and their effects, is crucial for the decision–making process on air quality management policies. Based on a compilation of regional and local AQP, a review of assessment capabilities and used modeling tools to evaluate the effects of emission abatement measures on the air quality and health was performed. In most cases, models are applied to estimate emissions and to assess the resulting air quality from both reference and emission abatement scenarios. Air quality’s impacts on the health and environment are rarely quantified. Regarding the air quality assessment, beyond the modeling, monitored data for validation of simulations are also used. Some studies, however, do not include the use of air quality models, considering the monitoring network as spatially representative of the study domain (e.g. Lisbon Region, Riga, Malta). In order to overcome methodological limitations for quantifying the impacts of emission abatement measures, economic evaluation techniques or even Integrated Assessment Methodologies (IAM) have been developed. IAM, already applied in some AQP or case studies, namely for Antwerp and London, are used for assessing how reductions in emissions contribute to improve air quality, reduce exposure and protect human health.